DIPLOMASI INDONESIA TERHADAP ARAB SAUDI DALAM MENINGKATKAN WISATAWAN MELALUI PARIWISATA HALAL TAHUN 2017-2019 - Anggia Sarasandy, (2021)
Halal tourism is a tourism segment that offers halal-certified services on all its products. The emergence of halal tourism is intended to meet the needs of Muslim tourists who have special needs such as halal food, places to worship, and sharia hotels. Halal tourism has been developed by several countries including Indonesia. The main purpose of developing halal tourism in Indonesia is to attract foreign tourists to come to Indonesia, especially tourists who are Muslim, including Saudi Arabia. But unfortunately, the number of Saudi Arabian tourists who come to Indonesia has continued to decline from 2017 to 2019 even though halal tourism has been developed and promoted. In this paper, the author will use three concepts namely, the concept of national interest to see Indonesia's interests in promoting tourism. The second concept is multi-track diplomacy which the author will use to analyze the diplomatic efforts made by Indonesia in promoting halal tourism in Saudi Arabia. The author focuses on the concept of multi-track diplomacy on two paths, namely the first path (government) and the third path (business). And the concept of halal tourism to explain the concept of tourism used in promoting Indonesian tourism in Saudi Arabia. In this paper, the author uses a qualitative case study method to provide an in-depth understanding of the diplomacy used by Indonesia to increase the number of Saudi Arabian tourists. Diplomacy analyzed in this paper is divided into two, namely, diplomacy carried out by the government and diplomacy carried out by the business sector. For diplomacy carried out by the government, the author explains four activities, namely holding a sales gathering, Wonderful Indonesia week, Familitrazion Trip (Fam trip), and participating in the Saudi Aramco Travel Show. Meanwhile, diplomacy carried out by the business sector is participating in the Jeddah International Travel & Tourism Exhibition, Riyadh Travel Fair, and conducting Sales Mission activities. Keywords: Halal Tourism, Saudi Arabia, Multi-track Diplomacy